Strategi Komunikasi Silang dalam Meningkatkan Kesadaran akan Keberadaan Tuli - Flavia Veilieta; Septia Winduwati (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2023)
Communication is something that happens every day in the society. But not everyone can communicate well because of their limitations, such as people with deaf disabled. In this study, the author used the word Deaf which begins with a capital letter to emphasize that Deafness is an identity, as people disabled who certainly have Human Rights, the